Penolakan Rektor Perguruan Tinggi Negeri dan Perguruan Tinggi Swasta atas Demands Deliverance Uang Kuliah Tahunan Mahasiswa yang Terdampak Akibat Virus Covid-19 - Edi Ribut Harwanto (Universitas Negeri Medan, 2021)
This study aims to determine the response of the leadership of PTS and PTN rectors throughout Indonesia regarding the full exemption of UKT for students who are affected by the Covid 19 virus and the impact of criminal and civil law on leaders or higher education institutions. In the context of this problem, the authors see from the optical psychology of law aspects in the legal review process, with two approaches to religious norms and an approach with positive legal norms. Furthermore, to support the purpose of this study, the paradigm used in this study is the post-positivism paradigm. The results of the study show that, based on the formulation of the criminal provisions of Law No.12 of 2012 on Higher Education, criminal provisions are regulated for those who commit criminal offenses. Meanwhile, regarding administrative sanctions for PTS and PTN higher education institutions that violate it, they are subject to administrative sanctions. Of the various administrative sanctions that have been regulated, there are also no rules for PTS and PTN to get sanctions, if they do not give full UKT exemption to students. What is regulated relating to students is only in Article 76 (1)